Motif Flora Dan Fauna Pada Candi Hindu Masa Kedatuan Sriwijaya Untuk Pembelajaran Sejarah - Susanti, Retno; Suhendi, Didi; Amalia, Ria; Wahyuni, Fadela Septi; Hudaidah, Hudaidah (Jurnal Penelitian Agama Hindu, 2025)
This study aims to explore the themes of flora and fauna motifs on Hindu temples during the Srivijaya period as part of the study of the history and art of religious architecture. The main objective is to understand how these motifs reflect the cosmology and spiritual values ​​of Hindu society during that period. The research methods used include descriptive analysis of temple reliefs in Sumatra, literature review of archaeological sources, and comparison with motifs on other Hindu temples in Southeast Asia. This analysis technique involves detailed observation of floral elements such as leaves, lotus flowers, and trees, as well as fauna such as birds, snakes, and mythological animals, which are often found on temple reliefs. The discussion focuses on the symbolic meaning of these motifs, where flora is often associated with fertility and life, while fauna symbolizes strength and wisdom. This study also discusses how these motifs function as a medium to convey spiritual values ​​and emphasize the harmonious relationship between humans and nature. The conclusion of this study shows that the flora and fauna motifs on Srivijaya Hindu temples not only function as aesthetic elements, but also have deep religious meanings. These motifs provide important insights into how the Srivijaya people combined their beliefs with a respect for nature, as well as their contribution to the understanding of Hindu history and culture in the archipelago.